Social Anxiety among Middle-Aged Teachers in Secondary Education Schools - Lihan Guo; Ratanaporn Awiphan; Tinakon Wongpakaran; Penkarn Kanjanarat; Danny Wedding (MDPI AG, 2024)
Background: This study aimed to investigate the prevalence of social anxiety symptoms (SASs) and its associated factors among middle-aged teachers in secondary education schools. Methods: A cross-sectional survey was conducted from December 2023 to March 2024 among 341 secondary education schoolteachers aged 45-59 in Chiang Mai, Thailand, involving an online survey. Effects of psychosocial variables on SASs were investigated, including attachment anxiety, attachment avoidance, neuroticism and extraversion personality traits, loneliness, perceived social stress, job burnout, and anxiety and depression. Multiple linear regression was used to identify predictors of SASs. Results: This study found that 98 out of 341 (28.7%) teachers presented SASs. Multiple linear regression analysis showed that marital status (β = 0.103, 95% CI [0.437, 3.404]), income (β = 0.087, 95% CI [0.049, 3.758]), extraversion (β = −0.179, 95% CI [−0.573, −0.198]), attachment anxiety (β = 0.165, 95% CI [0.106, 0.359]), attachment avoidance (β = 0.145, 95% CI [0.066, 0.243]), depression (β = 0.242, 95% CI [0.248, 0.862]), loneliness (β = 0.182, 95% CI [0.099, 0.580]), and perceived social stress (β = 0.235, 95% CI [0.131, 0.373]) were significant predictors of SASs, explaining 51.1% of the variance. Conclusion: This study discovered a relatively high prevalence of SASs among middle-aged secondary schoolteachers.